PENGARUH PENDEKATAN MATEMATIKA REALISTIK TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATA PELAJARAN MATEMATIKA PESERTA DIDIK SEKOLAH DASAR - Yuni Santika Rahayu; Arissona Dwi Indah Sari (JUSEDA, 2020)
This study aims to determine whether there is an influence of realistic mathematical approaches to the problem solving abilities of elementary school students in mathematics. This research is quantitative research using experimental methods. The population in this study were all class II elementary school students of Gending Elementary School, Kebomas, Gresik in 2018/2019 academic year, totaling 50 students. Sampling is done by using a total sampling technique where all members of the population become a sample of research with the details of 24 students in the control class (permanent learning using the scientific approach) and 26 students in the experimental class (learning using realistic mathematical approaches). Data collection instruments use the problem solving ability test sheet with comparative analysis for data analysis techniques.Based on the results of data analysis that has been done, the hypothesis test (t test) shows that the significance value obtained is 0.001 smaller than 0.05. That is, there are significant differences in problem solving abilities using realistic mathematical approaches. Besides that, it can be seen from the average value of the control class problem solving ability test of 72.92 with the lowest value of 40 and the highest value of 96.67, while the experimental class gets an average of 87.18 with the lowest value of 50 and the highest value of 100. Which can be taken from this study is because there is a significant difference in the ability of problem solving using realistic mathematical approaches, then there is a significant influence on the use of realistic mathematical approaches to students' problem solving abilities.